Effect of catheter needle caliber on polidocanol foam stability in foam sclerotherapy - Azmoun, Sajjad; Liu, Yiran; Tursun, Medina; Liu, Shaohua (Frontiers in Neurology, 2024)
Although sclerotherapy is widely used to treat vascular malformations (VMs), it is associated with several challenges. One significant issue is the insufficient understanding of the influence of various factors on the stability of polidocanol (POL) foam used in sclerotherapy.This study aimed to explore the effect of the catheter needle caliber on foam stability when using POL with or without hyaluronic acid (HA) for the treatment of VMs.The Tessari method generated sclerosant foam using POL both with and without HA. We used catheters and syringe needles of various calibers, and the resulting foam was transferred into new syringes to facilitate a comparison of foam stability. Foam half-life (FHT) was utilized as a metric to assess foam stability.The study found that narrower needle calibers produced a more stable foam when POL was used alone; however, no significant effect was observed when HA was added. Furthermore, when the foam was expelled using catheters and syringe needles of the same size, no noticeable changes in the stability were observed.When choosing needles of varying calibers, their effect on foam stability should be carefully considered, particularly when the foam contains HA.